Perception of Telephone-Assisted Cardiopulmonary Resuscitation Among Emergency Medical Personnel in China: A Web-Based Survey - Kang, Xuqin; Lou, Jing; Tian, Sijia; Niu, Shengmei; Zhang, Luxi; Lian, Huixin; Zhang, Jinjun (Cardiology and Cardiovascular Medicine, 2022)
Objectives: To investigate the perception on Telephone-Assisted Cardiopulmonary Resuscitation (T-CPR) after Out-Of-Hospital Cardiac Arrest (OHCA) among Emergency Medical Service (EMS) providers in China. Methods: A multicentre, cross-sectional, descriptive, online questionnaire survey study was conducted on the perception among emergency centres in various regions across China from December 2018 to June 2019. Answers to questions concerning baseline characteristics of survey respondents, cognition and implementation of T-CPR, and use of automated external defibrillators were surveyed. Results: Of 1,191 questionnaires obtained from 15 provinces in China, 1,187 were valid. Among the 1,187 respondents, the mean age was 32.1±7.2 (20–60)years; 436 (36.7%) were male and 751 (63.3%)female; there were 256 dispatchers, 494 emergency doctors, 400 emergency nurses, and 37 medical emergency assistants; 960 (80.9%) had previously learned T-CPR and 227 (19.1%) had not. Of the 960 participants who knew T-CPR, 796 (82.9%) recognised cardiac arrest (CA), 714 of whom (89.7%) would further implement T-CPR. The difference in the cognition rate of T-CPR was statistically significant among EMS providers from 54.1% to 91.0% (chi-square test, 38.1; P<.001). In multivariate analysis, dispatchers had a significantly improved knowledge of T-CPR as their workload increased (P<.001; OR=1.002; 95%CI, 1.001–1.003). Conclusion: Substantial and important differences in the perception and implementation of T-CPR among EMS personnel were observed throughout China. Further professional training in T-CPR is urgently required for improvement in outcomes of OHCA countrywide.